Design of Digital Education Systems - N. I. Listopad; E. A. Bushchik (Цифровая трансформация)
An analysis of the main approaches to the design of information education systems is presented. The basics of designing information education systems (IES) are considered, taking into account the modern requirements of digital transformation. The principles of designing the IES are formulated, the basic requirements for the IES are developed, the types of activities that are planned to be carried out in electronic (digital) form are described. The authors show that the expected results from the introduction of the IES will affect all participants in the educational process, however, for each of these participants, these effects will be different. Models for designing the IES in the form of an infological model, a datalogical model, a physical model are proposed. Additionally, a model for designing the IES when teaching a particular discipline, as well as a model for constructing ER-diagrams, were considered. At the same time, the IES is a complex task and it should solve the problems of managing the educational process, automate, and optimize it.